Location theory based bio-energy systems planning in site optimisation modelling – Manicaland (Zimbabwe) - Makacha, Liberty (Midlands State University, 2018)
In as much as decision makers increasingly are turning to Geographical Information Systems to assist them with solving complex spatial problems, these systems on their own do not adequately support decision making because they are lacking in analytical modelling capabilities, do not easily accommodate variations in either the context or the process of spatial decision making. One response to these shortcomings is the development of spatial optimisation modelling techniques which are explicitly designed to address complex spatial problems. The design of such systems, with particular reference to least cost site selection using Analytic Hierarchy Process Modelling in Weighted Overlay Analysis, the decision making processes they support, and a framework for their implementation and subsequent evolution are examined in this research. The theme of the research can best be summed up in the statement “Multi-criteria assessment in GIS environments for the location of biomass power plants using Landsat8 imagery, for the estimation of above Ground Biomass (AGB) in Zimbabwe’s Eastern Districts, with a view to spatially identify least cost sites for the installation of biomass power plants to support renewable energy generation – improving the current energy mix and countering induced deficits from hydro power plants.” The research managed to identify areas suitable for facility location using the available datasets. However in the availability of more datasets a more informed site location can be achieved.